2010
DOI: 10.1364/josab.27.000730
|View full text |Cite
|
Sign up to set email alerts
|

IR permittivities for silicides and doped silicon

Abstract: The complex permittivity for Pt, Pd, Ni, and Ti-silicide films as well as heavily doped p-and n-type silicon were determined by ellipsometry over the energy range 0.031 eV to 4.0 eV. Fits to the Drude model gave bulk plasma and relaxation frequencies. Rutherford backscattering spectroscopy, X-ray diffraction, scanning electron microscopy, secondary ion mass spectrometry, and four-point probe measurements complemented the optical characterization. Calculations from measured permittivities of waveguide loss and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 26 publications
0
42
0
Order By: Relevance
“…Examples of intermetallics are the silicides and germanides, [19][20][21] often formed by sequentially deposited semiconductors (silicon or germanium, respectively) and metals (Cu, Co, Pd, Pt, Ni, Ti, for example) followed by a high temperature anneal to form a conducting material. While the majority of silicide and germanide research has focused on integration into CMOS fabrication technology, such materials are also of particular interest for longer-wavelength plasmonic applications, 22 due to their CMOS compatibility, and plasmonic behavior at frequencies below the band-edge of Si or Ge (and thus spectrally separated from interband absorption losses). Figure 3 shows the experimental and Drude model permittivity for representative silicide materials (NiSi and TiSi), from Ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of intermetallics are the silicides and germanides, [19][20][21] often formed by sequentially deposited semiconductors (silicon or germanium, respectively) and metals (Cu, Co, Pd, Pt, Ni, Ti, for example) followed by a high temperature anneal to form a conducting material. While the majority of silicide and germanide research has focused on integration into CMOS fabrication technology, such materials are also of particular interest for longer-wavelength plasmonic applications, 22 due to their CMOS compatibility, and plasmonic behavior at frequencies below the band-edge of Si or Ge (and thus spectrally separated from interband absorption losses). Figure 3 shows the experimental and Drude model permittivity for representative silicide materials (NiSi and TiSi), from Ref.…”
mentioning
confidence: 99%
“…Figure 3 shows the experimental and Drude model permittivity for representative silicide materials (NiSi and TiSi), from Ref. 22. As can be seen from the data in Fig.…”
mentioning
confidence: 99%
“…However, these materials are not useful in the infrared spectrum as their plasma frequency is typically in the UV or visible range [3,4]. For mid-wave infrared (MWIR, 3-5μm) and longwave infrared (LWIR, 8-12μm) applications, materials such as doped silicon and germanium [5,6], transparent conducting oxides [7], metal silicides [5,8] and metal germanides [9] have been investigated. A comprehensive review of these materials can be found in [2].…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of alternative plasmonic materials has recently been accelerated 7,[14][15][16][17][18][19][20][21][22][23][24][25][26] due to the push to the infrared where noble metals are not as useful due to weak mode confinement and lack of CMOS compatibility. Two promising candidates, aluminum and gallium doped ZnO, have been proposed as possible plasmonic materials in the near- 17,19 and mid-IR 26 as these materials typically demonstrate plasma wavelengths $1 lm.…”
Section: Introductionmentioning
confidence: 99%